(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The World Health Organization (WHO) has issued a warning that antibiotic resistance is a problem that must be effectively addressed and controlled that it poses serious challenges to the existing healthcare system. Pan-drug-resistant (PDR) infections are caused by microbes that have evolved methods to withstand all forms of antimicrobial treatment, such as those that impede drug absorption, alter drug targets, inactivate drugs, or utilize efflux pumps. The importance of treating this sort of medication resistance is underscored by the fact that the development of new therapies to treat it pushes clinicians to take action. Only a few numbers of antibiotics, particularly when used in combination, are successful against PDR Gram-negative bacteria such Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli. Treatment of PDR A. baumannii is best accomplished using tigecycline in collaboration with colestimethate, imipenem, or amikacin. The use of β-lactamase antagonists, including ceftolozanetazobactam or imipenem-cilastatin-relebactam, is the greatest effective method of treating PDR P. aeruginosa. Nitrofurantoin, fosfomycin, and pivmecillinam appear to be the best successful medication for the treatment of PDR E. coli, whereas tigecycline and colistin have been used to treat PDR K. pneumoniae throughout the last several decades. Despite the fact that these medications fight PDR infections quite well, there is a pressing need for the development of new substances and techniques of countering resistance since antibiotic resistance is increasing every day in microbial species throughout the globe.